Management of a Gastrobronchial Fistula Connected to the Skin in a Giant Extragastric Stromal Tumor - Emilio Muñoz; Fernando Pardo-Aranda; Noelia Puértolas; Itziar Larrañaga; Judith Camps; Enrique Veloso (Case Reports in Surgery)
Introduction. Gastrointestinal stromal tumors first treatment should be surgical resection, but when metastases are diagnosed or the tumor is unresectable, imatinib must be the first option. This treatment could induce some serious complications difficult to resolve. Case Report. We present a 47-year-old black man with a giant unresectable gastric stromal tumor under imatinib therapy who presented serious complications such as massive gastrointestinal bleeding and a gastrobronchial fistula connected with the skin, successfully treated by surgery and gastroscopy. Discussion. Complications due to imatinib therapy can result in life threatening. They represent a challenge for surgeons and digestologists; creative strategies are needed in order to resolve them.